Sistem Pelayanan dan Pemesanan Online pada Toko Bangunan Sumarno Jaya Depok - Rahnita Nuzulah (Universitas Indraprasta PGRI Jakarta, 2018)
The existence of Sumarno Jaya Store Building is very helpful to people, especially those who are building houses in Depok. The store receives orders of building materials, products and others. However, there are many people not knowing it because it is not a big store. Therefore, with the use of internet media, it is expected that many people will know the Building Shop Sumarno Jaya.. The purpose of the research is to make consumers easily access the services and order building products without coming to the store and to make the store owners improve the service, order and promotion to develop and expand the store in the future. In this modern era, technology competition is getting tougher, especially in cyberspace or better known as internet. It is a new challenge encouraging the researcher to be enthusiastic about competing in this Globalization Era. Application used by the researcher to design the website is Content Management System (CMS), with PHP programming language and MYSQL database. Thus, a website application will look like a mere desktop application. Then, the level of speed, interactivity, functionality, and usefulness of web pages will increase.